Cosx - Sinx = Cos2x
Cosx - Sinx - (Cos²x - Sin²x) = 0
(Cosx - Sinx) - (Cosx - Sinx)(Cosx + Sinx) = 0
(Cosx - Sinx)(1 - Cosx - Sinx) = 0
1) Cosx - Sinx = 0
Разделим обе части на Cosx ≠ 0, получим :
1 - tgx = 0
tgx = 1
n∈z
2) 1 - Cosx - Sinx = 0
Cosx + Sinx = 1
Разделим обе части на корень из двух, получим :
![\frac{1}{\sqrt{2}}Cosx+\frac{1}{\sqrt{2}}Sinx=\frac{1}{\sqrt{2}}}\\\\Cos\frac{\pi}{4}Cosx+Sin\frac{\pi}{4}Sinx=\frac{1}{\sqrt{2}} \\\\Cos(x-\frac{\pi}{4})=\frac{1}{\sqrt{2}}\\\\x-\frac{\pi}{4}=+-arcCos\frac{1}{\sqrt{2}} +2\pi n\\\\ x-\frac{\pi}{4}=+-\frac{\pi}{4}+2\pi n\\\\x_{1}=\frac{\pi}{2} +2\pi n\\\\x_{2}=2\pi n \frac{1}{\sqrt{2}}Cosx+\frac{1}{\sqrt{2}}Sinx=\frac{1}{\sqrt{2}}}\\\\Cos\frac{\pi}{4}Cosx+Sin\frac{\pi}{4}Sinx=\frac{1}{\sqrt{2}} \\\\Cos(x-\frac{\pi}{4})=\frac{1}{\sqrt{2}}\\\\x-\frac{\pi}{4}=+-arcCos\frac{1}{\sqrt{2}} +2\pi n\\\\ x-\frac{\pi}{4}=+-\frac{\pi}{4}+2\pi n\\\\x_{1}=\frac{\pi}{2} +2\pi n\\\\x_{2}=2\pi n](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B%5Csqrt%7B2%7D%7DCosx%2B%5Cfrac%7B1%7D%7B%5Csqrt%7B2%7D%7DSinx%3D%5Cfrac%7B1%7D%7B%5Csqrt%7B2%7D%7D%7D%5C%5C%5C%5CCos%5Cfrac%7B%5Cpi%7D%7B4%7DCosx%2BSin%5Cfrac%7B%5Cpi%7D%7B4%7DSinx%3D%5Cfrac%7B1%7D%7B%5Csqrt%7B2%7D%7D+%5C%5C%5C%5CCos%28x-%5Cfrac%7B%5Cpi%7D%7B4%7D%29%3D%5Cfrac%7B1%7D%7B%5Csqrt%7B2%7D%7D%5C%5C%5C%5Cx-%5Cfrac%7B%5Cpi%7D%7B4%7D%3D%2B-arcCos%5Cfrac%7B1%7D%7B%5Csqrt%7B2%7D%7D+%2B2%5Cpi+n%5C%5C%5C%5C+x-%5Cfrac%7B%5Cpi%7D%7B4%7D%3D%2B-%5Cfrac%7B%5Cpi%7D%7B4%7D%2B2%5Cpi+n%5C%5C%5C%5Cx_%7B1%7D%3D%5Cfrac%7B%5Cpi%7D%7B2%7D+%2B2%5Cpi+n%5C%5C%5C%5Cx_%7B2%7D%3D2%5Cpi+n+++++++++)